The impact of TQM practices on learning organisation and customer orientation: a survey of small service organisations in Malaysia - Ang, Yueh Sin; Lee, Voon Hsien; Tan, Boon In; Chong, Alain Yee Loong* (Inderscience Enterprises Ltd., 2011)
The purpose of this paper is to examine the impact of Total Quality Management (TQM) practices on customer orientation and learning organisation in Malaysian service sector. This study was based on empirical data collected from a survey of 122 managers of Malaysian service firms. Correlation analysis and multiple regression analysis were used to examine the proposed model. The results found that process management was perceived as a dominant TQM practice in improving firms' learning organisation and customer orientation. The results of this paper can be used by top management to prioritise the implementation of TQM practices. For instance, those dimensions that are found to have positive influence on customer orientation and learning organisation can be recommended to top management so that they can allocate resources to improve these practices to achieve higher customer orientation and learning organisation within the service firms in Malaysia.